2010
DOI: 10.1186/1471-2164-11-53
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of predicted non-coding RNAs in Rhizobium etli expressed during free-living and host-associated growth using a high-resolution tiling array

Abstract: BackgroundNon-coding RNAs (ncRNAs) play a crucial role in the intricate regulation of bacterial gene expression, allowing bacteria to quickly adapt to changing environments. In the past few years, a growing number of regulatory RNA elements have been predicted by computational methods, mostly in well-studied γ-proteobacteria but lately in several α-proteobacteria as well. Here, we have compared an extensive compilation of these non-coding RNA predictions to intergenic expression data of a whole-genome high-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
63
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 63 publications
5
63
0
2
Order By: Relevance
“…Recent high-throughput analyses revealed that these α-proteobacterial species harbor hundreds of RNAs with regulatory potential. [5][6][7][8][9][10][11][12] It is the challenge now to understand their physiological roles and the underlying molecular mechanisms. A systematic comparison of the sRNA repertoires of selected model organisms may help to understand the commonalities and differences between these phylogenetically and ecologically related bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent high-throughput analyses revealed that these α-proteobacterial species harbor hundreds of RNAs with regulatory potential. [5][6][7][8][9][10][11][12] It is the challenge now to understand their physiological roles and the underlying molecular mechanisms. A systematic comparison of the sRNA repertoires of selected model organisms may help to understand the commonalities and differences between these phylogenetically and ecologically related bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…This view is supported by the large amount of cis-and trans-encoded sRNAs detected by genome-wide analyses in these plant-associated bacteria. [5][6][7][8][9][10][11][12] Since conservation of sRNAs is mostly limited to closely related bacteria, the phylogenetic relationships between α-rhizobia and Agrobacterium species allow the functional comparison of sRNAs with different degrees of conservation in function and regulation. Here, we summarize the current knowledge on the non-coding RNome as inferred from genome-wide surveys and discuss the incipient insights into biological functions and mechanisms of riboregulation in these organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the identification of a number of genes potentially involved in rhizosphere competence in the A1501 genome, little is known about the mechanisms of adaptation and survival in the rhizosphere (17). A search for ncRNAs in other nitrogen-fixing organisms was reported (5,6,14,(27)(28)(29), but none have been described so far as being involved in the regulation of nif gene expression.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28] Changes in the amount of some of the sRNAs under different stresses, in different media, and at different growth stages suggest that they are involved in adaptation to stress, changing environmental conditions and in symbiosis. [23][24][25][26][27][28] In the a-proteobacterium Agrobacterium tumefaciens the sRNA AbcR1, which is homologous to the Hfq-dependent sRNA SmrC16 of S. meliloti, controls the expression of a periplasmic substrate binding protein required for uptake of the plant-derived defense signal GABA. 22,23,29 Here we describe the prediction, verification and analysis of seven novel sRNAs in the Bradyrhizobium/Rhodopseudomonas lineage.…”
mentioning
confidence: 99%